The Effect of Pearl Oyster (Pinctada maxima L.) Biofouling Waste Organic Fertilizer and Watering Interval on The Growth and Results of Mustard Greens (Brassica juncea L.) - Nendissa, Jeanne Ivonne; Riry, Johan; Amba, Martha; Soplanit, Rudy (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research was conducted in Pelita Jaya Village, Pohon Batu Hamlet, West Seram Regency from June to July 2022. The research was conducted to study the effect of the interaction of doses of organic fertilizer from pearl oyster biofouling waste and intervals of water administration on the growth and yield of mustard plants. The design used in this study was a factorial randomized group trial design (RAK) with two treatments as follows: Factor I: Pearl Oyster Biofouling Waste Fertilizer (L) with 4 levels, namely L0 = Control, L1 = Dosage of 50 gr/tan, L = 100 g/tan and L3 = 150 gr/tan Factor II : Watering Time Interval (W) namely W1 = 1 day, W2 = 2 days and W3 = 3 days. Each treatment was combined to obtain 12 treatments with 3 replications, resulting in 36 experimental plots. In each plot, 4 sample plants were taken so that in total there were 144 sample plants. The results of this study indicate that the interaction of organic fertilizer from pearl oyster biofouling waste with intervals of watering has a very significant effect on the growth and yield of mustard plants (number of leaves, leaf area, plant fresh weight and plant dry weight). The best treatment interaction was the combined dose of pearl oyster biofouling waste fertilizer 150 g/tan with an interval of watering once every three days for mustard greens (Brassica juncea L.)